2012
DOI: 10.1590/s1984-46702012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of introduced sessile species on the near shore continental shelf in southern Brazil

Abstract: ABSTRACT. Invasion by marine species, often considered a grave threat to marine ecosystems, occurs throughout the world as a consequence of many anthropogenic activities. In coastal Paraná, many factors including shipping, aquaculture and the use of artificial substrates provide suitable environments for the establishment and rapid spread of introduced marine species. To better understand this process, the encrusting community was studied on polyethylene plates (n = 120, 10 x 10 cm) that were placed seasonally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 46 publications
0
15
0
2
Order By: Relevance
“…(Rocha & Faria 2005). Also, the NIS Ascidia tenue Monniot, 1983 was only found on recruitment plates in /2009(Bumbeer & Rocha 2012. Usually, NIS populations fluctuate widely, so the absence of a few in the present study was not that surprising.…”
Section: Dzup-symp52mentioning
confidence: 44%
See 3 more Smart Citations
“…(Rocha & Faria 2005). Also, the NIS Ascidia tenue Monniot, 1983 was only found on recruitment plates in /2009(Bumbeer & Rocha 2012. Usually, NIS populations fluctuate widely, so the absence of a few in the present study was not that surprising.…”
Section: Dzup-symp52mentioning
confidence: 44%
“…However, that being said, these two types of substrate still had 45 species in common. Two prior studies at the Currais MPA used recruitment plates to evaluate colonization of invertebrates (Brandini & Silva 2011, Bumbeer & Rocha 2012, including time in their survey of species. Those studies found mostly pioneer species, that are likely to be due to propagule supply rather than to the already developed community.…”
Section: Dzup-symp52mentioning
confidence: 99%
See 2 more Smart Citations
“…This is in part a consequence of anthropogenic transport of species to areas beyond their native habitats and natural home ranges, mainly by ballast water and fouling of hulls of ships and oceanic platforms (MARINS et al 2010, BUMBEER & ROCHA 2012. Shipping activities are recognized as the main source of species' introductions in marine habitats (MACKIE et al 2006, IGNACIO et al 2010, BUMBEER & ROCHA 2012, and in the Atlantic, the number of non-indigenous marine fouling species is increasing, especially in ports and harbors (MCCANN et al 2007, MARINS et al 2010.…”
mentioning
confidence: 99%